Diversity, Composition, and Activities of Nano- and Pico-Eukaryotes in the Northern South China Sea With Influences of Kuroshio Intrusion - Wang, Feipeng; Huang, Bangqin; Xie, Yuyuan; Cai, Shujie; Wang, Xiuxiu; Mu, Jingli (Frontiers in Marine Science, 2021)
Nano- and pico-eukaryotes play important roles in the diversity and functions of marine ecosystems. Warm, saline, and nutrient-depleted water that originates in the Kuroshio Current seasonally intrudes into the northern South China Sea (NSCS) from autumn to spring. To clarify the mechanisms in shaping the community structure of nano- and pico-eukaryotes as well as impacts of the Kuroshio intrusion on the NSCS ecosystem, genomic DNA and RNA were co-extracted from samples collected at two depths from nine stations, and then the V9 region of 18S rDNA and rRNA was sequenced with high-throughput sequencing. Our results showed that Dinophyceae was the most diverse and abundant nanoeukaryotic group during the study period revealed by both DNA and RNA surveys. In contrast, the relative read abundance of MAST, Pelagophyceae, and Dinophyceae in the size fraction of picoeukaryotes might be largely underestimated by the DNA survey. The RNA survey was the more reliable method to investigate the eukaryotic community structure. Environmental filtering played an important role in shaping the community structure, and the sampling depth became the governing factor of the beta diversity under the environmental setting of stratification during the study period. The spatial variations in the diversity of nanoeukaryotes were subject to the dispersal limitation under the size rule. The effects of the Kuroshio intrusion on the nanoeukaryotic community structure might also be explained by the dispersal limitation. Overall, neutral processes are critical in shaping the community structure of nanoeukaryotes. The relative metabolic activities of nanoeukaryotes were relatively stable in accordance with the high similarity of community structure between sampling sites. The responses of the relative metabolic activities of picoeukaryotes to environmental factors displayed two distinct patterns: positive correlations with salinity and nutrients and negative with temperature for Dinophyceae, MAST, and Pelagophyceae, while reversed patterns for Mamiellophyceae and Radiolaria. Our findings improve the understanding of the nano- and pico-eukaryotic communities in the NSCS and the mechanisms of their assembly.